Association of DARS gene polymorphisms with the risk of isolated ventricular septal defects in the Chinese Han population. Issue 1 (December 2016) - Feng, Yu; Chen, Runsen; Mo, Xuming
Abstract Background Ventricular septal defects (VSD) are the most common subtype of congenital heart defects (CHD) and are estimated to account for 20 to 30% of all cases of CHD. The etiology of isolated VSD remains poorly understood. Eight core aminoacyl-tRNA synthetases (ARSs) (EPRS, MARS, QARS, RARS, IARS, LARS, KARS, and DARS) combine with three nonenzymatic components to form a complex known as the multisynthetase complex (MSC). Four single nucleotide polymorphisms (SNPs) in EPRS have been reported to be associated with risks of CHD in Chinese populations. Methods In this study, we hypothesize that SNPs of the DARS gene might influence susceptibility to sporadic isolated VSD. Therefore, we conducted a case-control study of 841 patients with isolated VSD and 2953 non-CHD controls from the Chinese Han population to evaluate how 4 potentially functional SNPs within the DARS gene were associated with the risk of VSD. Results We observed that the risk of VSD was significantly associated with rs2164331 [G/A; odds ratio (OR) = 0.78, 95% confidence interval (CI) = 0.69-0.91; P = 3.17 × 10-3 ], rs6738266 [G/A; OR = 1.17, 95% CI = 1.05-1.29, P = 1.83 × 10-3 ], and rs309143 [G/A; OR = 1.09, 95% CI = 1.01-1.17; P = 3.12 × 10-2 ]. Additionally, compared with individuals with 0-2 risk alleles, individuals carrying 3, 4, and 5 or more risk alleles had 1.01-, 1.22- and 1.46-fold greater risks of VSD, respectively. These findings revealed a significant dose-response effect for VSD risk among individuals carrying different numbers of risk alleles (Ptrend = 6.37 × 10-4 ). Conclusions These findings indicate that genetic variants of theDARS gene may influence individual susceptibility to isolated VSD in the Chinese Han population.